PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PT. BANK CENTRAL ASIA Tbk. KANTOR CABANG SUBANG - Hanifa, Sapira; Oktafani, Farah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
Every company needs human resources that are able to survive and play an active role in the success of said company. Therefore, companies need employees that have a high level of performance that determines the success or failure of the company's goals. Expectations for high employee performance cannot be separated from employees stress work condition as well as at PT. Bank Central Asia Tbk. Branch Office Subang. This study aims to determine the effect of work stress on employee performance at PT Bank Central Asia Tbk. Branch Office Subang. Variables used in this research are work stress (X) and employees performance (Y) This type of research is descriptive uses causal approach and quantitative methods, with 91 employees as saturated samples. Sampling was done by the non-probability method. Analysis of the data used is descriptive analysis and simple linear regression. Based on the results of the study, it can be concluded that work stress is at high categories and employees performance classified in a good category. The t-test shows that work stress has a significant effect on employee performance and the determination coefficient says that work stress on employees performance is 46.3% while the remaining 53.7% is influenced by other factors not examined in this study.